Research progress on chromothripsis and tumorigenesis - MENG Huanliang, MU Haoran, JIANG Yafei, TIAN Kai, HE Enjun, HUA Yingqi (Zhongguo aizheng zazhi, 2023)
Chromothripsis is a complex genomic rearrangement event in which localized regions of one or several chromosomes fragment in response to stress (ionizing radiation, chemical stimulation, infection, etc.) and then assembles in random order. In recent years, through whole genome sequencing, single nucleotide polymorphism array, comparative genome hybridization and other technologies, it has been found that such highly complex genomic aberration events are common in all types of tumors, and they occur more frequently in sarcoma and nervous system tumors. The mechanism of chromothripsis is not clear, and there are two main mechanisms of chromothripsis formation: ① Formation of micronuclei and fragmentation of chromosomes in micronuclei; ② Generation of breakage-fusion-bridge cycles. Chromothripsis is catastrophic for the vast majority of cells, but some cells still survive this process. The fragmented chromosome fragments in cells are randomly combined to cause genome rearrangement through non-homologous end-joining, alternative end joining and microhomology-mediated break-induced replication. Oncogene amplification, tumor suppressor gene deletion or fusion gene formation may occur in the rearranged genome, which endowing cells with significant selective growth advantages and promoting the occurrence and development of tumors. Some criteria have been proposed to infer whether chromothripsis occurs in the genome. Recent clinical cohort studies have shown that the clinical prognosis of cancer patients is also related to the frequency of chromothripsis. The higher the frequency of chromothripsis, the worse the prognosis. The prevalence and poor prognosis of chromothripsis in tumors suggest that detection of chromothripsis may be a way to evaluate the survival and prognosis of cancer patients. It has been found that chromothripsis plays an important role in the occurrence and development of tumors, however, the causes of chromothripsis, the mechanism of tumorigenesis, the diagnosis and treatment of chromothripsis remain to be further studied. With the answers to the related questions of chromothripsis, it will be helpful to better understand the role of chromothripsis in tumor progression, and provide a new theoretical basis for the prevention and treatment of cancer. This article reviewed the research progress of chromothripsis and tumorigenesis.